DINAMIKA KEPEMIMPINAN DALAM PENGAMBILAN KEPUTUSAN CEPAT DI BADAN PENANGGULANGAN BENCANA DAERAH ( BPBD) PROVINSI SUMATERA BARAT - Zahra Meisya Saharyani; Syamsir; Teraya Dewiayus Khasturi; Rina Wahyuni; Rista Ningsih; Salma Afal Alshadiqa; Suci Ramadhani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze leadership dynamics in rapid decision-making within the Regional Disaster Management Agency (BPBD) of West Sumatra Province. The background of this research is based on the high level of disaster vulnerability in the region, which requires adaptive and responsive leadership in emergency situations. This research employs a qualitative descriptive approach using observation, interviews, and documentation techniques. The findings reveal that leadership in emergency situations is characterized by the ability to manage time pressure, limited information, and cross-sector coordination. Furthermore, the implementation of collaborative and transformational leadership plays a significant role in improving decision-making effectiveness. These findings indicate that leadership flexibility and communication skills are key factors in successful disaster management.Keywords: leadership; decision making; disaster management; BPBD; collaboration